Physiological Responses Induced by Manual Therapy in Animal Models: A Scoping Review - Lima, Carla Rigo; Martins, Daniel Fernandes; Reed, William Ray (Frontiers in Neuroscience, 2020)
Background: Physiological responses related to manual therapy (MT) treatment have been investigated over decades using various animal models. However, these studies have not been compiled and their collective findings appraised. The purpose of this scoping review was to assess current scientific knowledge on the physiological responses related to MT and/or simulated MT procedures in animal models so as to act as a resource to better inform future mechanistic and clinical research incorporating these therapeutic interventions. Methods: PubMed, Cumulative Index to Nursing and Allied Health Literature (CINAHL), Cochrane, Embase and Index of Chiropractic Literature (ICL) were searched from database inception to August 2019. Eligible studies were: (a) published in English; (b) non-cadaveric animal-based; (c) original data studies; (d) included a form of MT or simulated MT as treatment; (e) included quantification of at least one delivery parameter of MT treatment; (f) quantification of at least one physiological measure that could potentially contribute to therapeutic mechanisms of action of the MT. MT studies were categorized according to three main intervention types: (1) mobilization; (2) manipulation; and (3) massage. Two-phase screening procedures were conducted by a pair of independent reviewers, data were extracted from eligible studies and qualitatively reported. Results: The literature search resulted in 231 articles of which 78 met inclusion criteria and were sorted by intervention type. Joint mobilization induced changes in nociceptive response and inflammatory profile, gene expression, receptor activation, neurotransmitter release and enzymatic activity. Spinal manipulation produced changes in muscle spindle response, nocifensive reflex response and neuronal activity, electromyography and immunologic response. Physiological changes associated with massage therapy included autonomic, circulatory, lymphatic and immunologic functions, visceral response, gene expression, neuroanatomy, function and pathology, and cellular response to in vitro simulated massage. Conclusion: Pre-clinical research supports an association between MT physiological response and multiple potential short-term MT therapeutic mechanisms. Optimization of MT delivery and/or treatment efficacy will require additional preclinical investigation in which MT delivery parameters are controlled and reported using pathological and/or chronic pain models that mimic neuromusculoskeletal conditions for which MT has demonstrated clinical benefit.